‘An unbidden guest at your table’: Purity, danger and the house-fly in the middle-class home, c. 1870-1910 - Neil Davie (Cahiers Victoriens et Edouardiens)
The house-fly was an inescapable part of everyday life in Victorian England, and its presence in the home was an unwelcome reminder to middle-class Victorians that for all their efforts to construct the domestic space as a pristine refuge from the external forces of disorder, pollution and dirt, there was no escaping this atavistic symbol of filth and disease. Despite improvements in public health in the second half of the nineteenth century, the preoccupation with flies in late-Victorian England intensified rather than eased. This reflected in part changing environmental conditions conducive to the proliferation of flies, but also new attitudes, particularly among middle-class urbanites, towards the organisation of public space, and the place of animals within it. This in turn reflected contemporary developments in medical and biological science; along with broader attitudes to ‘cleanliness’ and ‘dirt’. This article will examine the roots of the ‘house-fly danger’ in late-Victorian England, exploring contemporary debates in both the scientific literature and the popular press, and will discuss the surprisingly diverse ramifications of public concern about these insects. It will be argued that the growing hygienist focus on flies as airborne carriers of disease co-existed, particularly in the earlier part of the period, with older more benign, attitudes to the house-fly, linked to the theories of natural theology.